2010
DOI: 10.1074/jbc.m109.074906
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Association of PIPKIγ-p90 with Clathrin Adaptor AP-2

Abstract: Phosphatidylinositol 4,5-bisphosphate (PI(4,5)P 2 ) is an essential determinant in clathrin-mediated endocytosis (CME). In mammals three type I phosphatidylinositol-4-phosphate 5-kinase (PIPK) enzymes are expressed, with the I␥-p90 isoform being highly expressed in the brain where it regulates synaptic vesicle (SV) exo-/endocytosis at nerve terminals. How precisely PI(4,5)P 2 metabolism is controlled spatially and temporally is still uncertain, but recent data indicate that direct interactions between type I P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…PIPKIci2 and PIPKIci5 are expressed in the majority of epithelial and nonepithelial cell lines, where they have unique functions. PIPKIci2 regulates the trafficking of several proteins to and from the plasma membrane (Bairstow et al, 2006;Kahlfeldt et al, 2010;Ling et al, 2007). The function of PIPKIci5 is still emerging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PIPKIci2 and PIPKIci5 are expressed in the majority of epithelial and nonepithelial cell lines, where they have unique functions. PIPKIci2 regulates the trafficking of several proteins to and from the plasma membrane (Bairstow et al, 2006;Kahlfeldt et al, 2010;Ling et al, 2007). The function of PIPKIci5 is still emerging.…”
Section: Discussionmentioning
confidence: 99%
“…Specific isoforms have distinct functions. For example, PIPKIci2 regulates focal adhesion dynamics and vesicle trafficking (Di Paolo et al, 2002;Kahlfeldt et al, 2010;Ling et al, 2002). In epithelial cells, PIPKIci2 regulates the formation of cell-cell contacts through its association with the adhesion molecule E-cadherin and a specific interaction with the epithelial-specific AP1B clathrin adaptor complex .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of these mice revealed a reduction in PtdIns(4,5)P 2 levels in brain accompanied by synaptic vesicle (SV) recycling defects. As PIPKIc interfaces with the clathrin-endocytosis machinery via interactions between the AP-2 adaptor complex and either the Cterminal extension present in PIPKIc_i2 (Bairstow et al, 2006;Nakano-Kobayashi et al, 2007;Thieman et al, 2009;Kahlfeldt et al, 2010) or the kinase domain (Krauss et al, 2006) we sought to confirm the findings in our PIPKIc 2/2 mouse and extend them to the PIPKIcDE17 mouse.…”
Section: Endocytosis Defects In Pipkicmentioning
confidence: 56%
“…PIPKIc_i2 was shown to be the relevant splice isoform in neurons (Nakano-Kobayashi et al, 2007) and was also shown to be an important mediator of endocytosis in MDCK and HeLa cells (Bairstow et al, 2006). Mutational and structural analysis indicates that the 26 amino acid extension of PIPKIc_i2 binds to the m2 subunit of the AP-2 adaptor complex (Bairstow et al, 2006;Kahlfeldt et al, 2010), as well as to the b2 subunit (Nakano- Kobayashi et al, 2007;Thieman et al, 2009;Kahlfeldt et al, 2010), thereby localizing PIPKIc_i2 to clathrin-coated pits. However, the kinase core domain of all PIPKIs also binds to m2, raising the possibility that other PIPKIs and splice isoforms of PIPKIc may stimulate endocytosis in some cell types (Krauss et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation